2002
DOI: 10.1108/07363760210444841
|View full text |Cite
|
Sign up to set email alerts
|

Misplaced marketing The social harm of public service advertising

Abstract: The power of advertising is presumed and people behind most public service advertising campaigns see advertising itself as the solution. An advertising campaign that aims to serve a social goal faces many pragmatic obstacles. Advertising professionals contribute to this problem. Just because advertising sometimes can help generate consumer interest in specific brand names does not also mean that every advertised effort will get people to make significant changes in their behavior. The Advertising Council, “ded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Still a larger question is how well counter-marketing messages can work at all. Rotfeld (2002) observed that advertising is often presumed to hold near-magical powers in changing problematic behavior, although it seldom does. Rotfeld (1999) also argued that many campaigns have strategically attempted to use appeals to fear, most of which were ineffective at modifying behavior because campaign creators mistakenly believed in an "optimal level of fear," despite 45 years of mixed results.…”
mentioning
confidence: 99%
“…Still a larger question is how well counter-marketing messages can work at all. Rotfeld (2002) observed that advertising is often presumed to hold near-magical powers in changing problematic behavior, although it seldom does. Rotfeld (1999) also argued that many campaigns have strategically attempted to use appeals to fear, most of which were ineffective at modifying behavior because campaign creators mistakenly believed in an "optimal level of fear," despite 45 years of mixed results.…”
mentioning
confidence: 99%